Estimation of Salivary IL-6 Level in relation of Periodontal Status in Patients with Hyperthyroidism - Kadhom, Eman Habib; Radhi, Nada Jafer MH. (AL-Kindy College Medical Journal, 2023)
Background: The overproduction of thyroid hormones is known as hyperthyroidism. Increased susceptibility to caries and periodontal disease are two potential oral symptoms. The interleukin-6 (IL-6) was observed to significantly increased in the hyperthyroid group. According to multiple research, IL-6 dysregulation has been linked to a number of oral disorders, including periodontal diseases. The study aimed to evaluate periodontal health status in relation to IL6 among hyperthyroidism patients. Subjects and Methods: The sample was composed of 90 female patients aged 25-45 years attending endocrine disorder center in al-Najaf Governorate/Iraq which include hyperthyroid group and healthy group, the hyperthyroid patients were diagnosed by specialist and under treatment with carbimazole. The clinical examination of periodontal health status assessment was performed according to WHO (2013) in addition to evaluation the Plaque and gingival condition. The Saliva was collected to evaluate IL-6 concentrations. Results: The plaque index (PLI) in the study group was more than the control with a significant difference (P<0.05). The gingival index (GI) in the study was more than the control but with no significant difference (P>0.05). Both periodontal pocket depth (PPD) and clinical attachment loss (CAL) were higher in the study group than in the control group, with a significant difference. IL-6 was higher in the study group than in control with a significant difference. There was a positive non-significant correlation between PPD and CAL with IL-6 in hyperthyroid patients.